Combined Analysis of Gut Microbiota and Plasma Metabolites Reveals the Effect of Red-Fleshed Apple Anthocyanin Extract on Dysfunction of Mice Reproductive System Induced by Busulfan - Wang, Bin; Xu, Jihua; Jiang, Shenhui; Wang, Yanbo; Zhu, Jun; Zhang, Yugang (Frontiers in Nutrition, 2022)
Busulfan is currently an indispensable anti-cancer drug, but the side effects on male reproductive system are so serious. Meanwhile, red-fleshed apples are natural products with high anthocyanin content. In this research, we analyzed the effect of red-fleshed apple anthocyanin extract (RAAE) on busulfan-treated mice. Compared with the busulfan group, main plasma biochemical indicators were significantly improved after RAAE treatment. In addition, we found RAAE alleviated busulfan-disrupted spermatogenesis through improving genes expression which are important for spermatogenesis, such as DDX4, PGK2 and TP1. Furthermore, we found that RAAE increased beneficial bacteria Akkermansia and Lactobacillaceae, and significantly depleted harmful bacteria Erysipelotrichia. The correlation studies indicated that RAAE ameliorated busulfan-induced rise in LysoPC levels through regulating gut microbial community and their associated metabolites. In conclusion, this study extends our understanding of the alleviated effect of RAAE on busulfan-induced male reproductive dysfunction through regulating the relationships between gut microbiota and metabolites.